A Comprehensive Study of Cyber Crime Categories and Strategies for Prevention - Singh, Navdeep (Indian Journal of Computer Science, 2025)
In today’s rapidly evolving world, the emergence of technology and digitalization has transformed the way individuals communicate. People now possess the remarkable ability to connect with others virtually, irrespective of location and time. This advancement has effectively bridged distances, allowing conversations to take place across the globe at any moment. However, alongside these benefits, a darker side has emerged: Cyber Crime. As our dependence on digital platforms increases, so does the prevalence of criminal activities conducted online. Cybercrime encompasses a wide range of malicious actions, including identity theft, hacking, online fraud, and most recent one is digital arrest. These modern threats pose significant challenges to individuals and organizations alike and it becomes crucial to remain vigilant and adopt measures to protect ourselves from potential cyber threats. This study delves into the various categories of cyber crimes that have emerged in the digital age, exploring their characteristics and the impacts they have on individuals and organizations. Cyber crime encompasses a wide range of illicit activities that occur online, and understanding these categories is essential for developing effective prevention strategies.